Guidelines for the use and interpretation of palaeofire reconstructions based on various archives and proxies. (1st August 2018) - Remy, Cécile C.; Fouquemberg, Cécile; Asselin, Hugo; Andrieux, Benjamin; Magnan, Gabriel; Brossier, Benoît; Grondin, Pierre; Bergeron, Yves; Talon, Brigitte; Girardin, Martin P.; Blarquez, Olivier; Bajolle, Lisa; et al.
Abstract: We present a comparative analysis of fire reconstructions from tree rings and from wood charcoal preserved in forest soils, peat and lake sediments. Our objective is to highlight the benefits and limits of different archives and proxies to reconstruct fire histories. We propose guidelines to optimize proxy and archive choice in terms of spatial and temporal scales of interest. Comparisons were performed for two sites in the boreal forest of northeastern North America. Compared to others archives, tree-ring analysis remains the best choice to reconstruct recent fires (<1000 years). For longer periods (from several centuries to millennia), lake charcoal can be used to reconstruct regional or local fire histories depending on the method used, but the focus should be on historical trends rather than on the identification of individual fire events. Charcoal preserved in peat and soils can be used to identify individual fire, but sometimes cover shorter time periods than lake archives. Highlights: Boreal wildfire reconstructions from soil, peat and lake charcoal and from tree rings were compared. Multi-millennial fire histories are well reconstructed with lake charcoal. The Charcoal Size Distribution method best reconstructs local fire history from lake charcoal. Peat and soil charcoal are useful to identify individual local fires. Tree ring analyses are the best choice to reconstruct recent fires.